OS07.4.A Regorafenib in recurrent glioblastoma patients: a multicentric real-life study. (5th September 2022) - Bruno, F; Pellerino, A; Pronello, E; Palmiero, R; Polo, V; Vitaliani, R; Trincia, E; Internò, V; Porta, C; Soffietti, R; Rudà, R
Abstract: Background: Few options are still available for recurrent glioblastoma (GBM). In the Italian phase 2 REGOMA trial, regorafenib improved overall survival, as compared to lomustine, for GBM patients at first progression after chemoradiation. Here, we present the results of a real-life multicentre study that analysed clinical and radiological features, response to treatments, tolerability, and outcome of a cohort of GBM patients treated with regorafenib at first tumour progression. Patients and Methods: We enrolled GBM patients at first tumour progression in three Italian Institutions (Turin, Treviso, Bari). Regorafenib was administered following an escalation dose protocol (1st cycle: 80 mg/day for 2 weeks, then 120 mg/day for one week; 2nd cycle: 120 mg/day for 2 weeks, then 160 mg/day for one week; 160 mg/day from the 3rd cycle). MRI scans were obtained at baseline and every 3 months. Progression-free survival (PFS) and overall survival (OS) were defined as time from regorafenib initiation and disease progression or death. Results: From January 2020 to January 2022, 66 GBM patients were included. Median age was 60.0 years. MGMTp methylation was found in 30 patients (45.5%). First-line treatment consisted in chemoradiation in 61 (92.4%), in upfront TMZ (3, 4.5%) or RT alone followed by TMZ (2, 3.0%). Median dose was 120 mg/day 21q28 day, which was lower than that used in REGOMA trial (149 mg). Median PFS (mPFS) was 2.7 months (2.4 - 3.0 95% CI) and median OS (mOS) 7.1 months (5.4 - 8.9 95% CI). Best RANO response to regorafenib was partial response (PR) in 10 (15.1%), stable disease in 14 (21.2%), and progressive disease in 42 (63.7%) patients. All PRs were observed within the first three months of treatment. Patients who completed treatment up the 6th, 9th, and 12th cycles were 20, 3 and 2, respectively. Forty-six (69.7%) patients presented adverse events of any grade, and 21 (31.8%) grade III-IV toxicity. The most frequent adverse events were fatigue (33.3%), hand-foot syndrome (27.3%), and liver enzymes increase (15.2%). Two patients only (3.0%) interrupted regorafenib due to toxicity.In a multivariable analysis, factors significantly associated with disease progression were higher age ( p = 0.035) and absence of MGMT p methylation ( p = 0.024). Conclusion: In this real-life study on 66 patients, mPFS and mOS were similar to those of the 59 patients enrolled in the regorafenib arm of REGOMA trial (2.7 vs 2.0 months; 7.1 vs 7.4 months, respectively). However, we observed a higher rate of PRs as compared to REGOMA (15% versus 3.0%). Type and severity of adverse events were similar between the two studies. Moreover, we had a lower incidence of discontinuations of regorafenib due to toxicity, maybe attributable to the lower dose intensity.We are further analysing the data of MRI-perfusion, with the aim to explore whether it can predict an early response or progression in comparison to standard MRI.